Pengaruh Model Cooperative Learning Tipe Numbered Head Together Terhadap Hasil Belajar Siswa Di SMA Negeri 2 Tondano - Carolin Theresa Sihaloho; Orbanus Naharia; Jantje Ngangi (Konstanta : Jurnal Matematika dan Ilmu Pengetahuan Alam, 2024)
This research uses a quasi-experimental method with a pretest and post-test control group design research design. This research uses the Numbered Head Together Cooperative Learning model to improve student learning outcomes at SMA Negeri 2 Tondano for the 2022/20223 academic year. The sample in this study was class. The average post-test score obtained in the experimental class was 87.7, and the average in the control class was 78.1. The data analysis technique used is the t-test with the condition that the data comes from a normally distributed and homogeneous population—test normality using the Lililefors test and homogeneity. Based on the hypothesis of the research statistical data, a tcount of 2,730 was obtained. Based on the ttable with α=0.005 and degrees of freedom (dk) = n1 + n2 -2 =20+20-2= 38, By looking at the ttable, we get ttable = 1.688. So tcount is greater than ttable, namely tcount = 2,730 > ttable = 1,688. Thus, according to the test criteria, if tcount > ttable, then H0 is rejected, so hypothesis H1 is accepted, and it is concluded that there is an influence of using the Numbered Head Together model on student learning outcomes in the human respiratory system material at SMA Negeri 2 Tondano.